Study Of Asphalt Characteristics Using Fly Ash as a Substitute For Sand In Concrete Asphalt (AC – WC) Using The Marshall Test (RSNI M-01-2003) and Test Standards Specifications For Bina Marga Specifications 2018 Revision 2 - Muhammad Gunawan Perdana (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
Utilization of fly ash which is part of the residue from burning coal for power plants (PLTU), where the combustion products have the same size as sand. Asphalt concrete is a type of construction pavement consisting of a mixture of asphalt and aggregate, either with or without added materials. This research aims to determine the characteristic values ​​of asphalt using fly ash as a substitute for sand in AC – WC asphalt concrete with mixed variations of 25%, 50% and 75%. From the research results, the AC-WC mixture used according to the standard, namely the condition of 5.5% asphalt content, obtained a stability value of 1580kg, a VFB value of 79.00%, a VMA value of 15.50%, a VIM value of 3.40%, a MQ value of 550kg/mm ​​, flow value 2.90mm and density value 2.35. Tests with mixture variations of 25%, 50% and 75% obtained a maximum stability value of 1706.5kg at a variation of 25%, a maximum flow value of 3.54mm at a variation of 75%, a maximum VIM value of 6.90% at a variation of 75%, a maximum VMA value 17.68% at 75% variation, maximum VFB value 84.89% at 25% variation, maximum density value 2.38 at 25% variation and MQ value 605.33kg/mm ​​at 25% variation. From the results of a study of the characteristics of asphalt using fly ash as a substitute for sand in AC-WC concrete asphalt with a variation of 50% which meets the requirements of the 2018 General Specifications Revision 2.